Thermal analysis of GFRP-reinforced continuous concrete decks subjected to top fire - Hawileh, Rami A.; Rasheed, Hayder A. (My University, 2017)
This paper presents a numerical study that investigates the behavior of continuous concrete decks doubly reinforced with top and bottom glass fiber reinforced polymer (GFRP) bars subjected to top surface fire. A finite element (FE) model is developed and a detailed transient thermal analysis is performed on a continuous concrete bridge deck under the effect of various fire curves. A parametric study is performed to examine the top cover thickness and the critical fire exposure curve needed to fully degrade the top GFRP bars while achieving certain fire ratings for the deck considered. Accordingly, design tables are prepared for each fire curve to guide the engineer to properly size the top concrete cover and maintain the temperature in the GFRP bars below critical design values in order to control the full top GFRP degradation. It is notable to indicate that degradation of top GFRP bars do not pose a collapse hazard but rather a serviceability concern since cracks in the negative moment region widen resulting in simply supported spans.
Citation: Hawileh, R. A., & Rasheed, H. A. (2017). Thermal analysis of GFRP-reinforced continuous concrete decks subjected to top fire. International Journal of Advanced Structural Engineering. https://doi.org/10.1007/s40091-017-0168-7
Keywords: Finite elements; Thermal-stress analysis; GFRP bars; Fire simulation curves; Concrete cover; Design tables